Three versions of Galerkin's method applied to the static deflection of a stepped beam - Storch, Joel; Amato, Marco; Elishakoff, Isaac (Vietnam Journal of Mechanics, 2024)
This work deals with the application of Galerkin's method for stepped structures to evaluate the static deflection under distributed loading. In this study, we compare two different implementations of the well-known method to the exact analytical result in order to prove that only the second method is able to give a good approximation to the solution of the problem.